Developing High School Students’ Listening Skills in The Context of Multimodal English Communication by Means of a Moodle-Based Training Program - M. V. Danilin; L. A. Milovanova (Открытое образование (Москва))
The purpose of the study is to describe the training program as a technological way to implement the methodology of skills’ formation and development of listening skills in the conditions of English-language multimodal communication at the level of secondary general education based on authentic audio-video materials and LMS Moodle distance learning technology. The relevance of the issue is underlined by the necessity of ensuring successful pupils’ interactions in the context of intercultural multimodal communication where verbal and non-verbal languages are used interdependently to produce meaning. From the point of view of methods of teaching it means a high school student must possess skills allowing to perceive (both aurally and visually) and understand social actions in English which are marked by the communicative indirectness resulted from the interdependency of verbal and non-verbal signals in producing multimodal meaning.Materials and methods. Theoretical justification of the development of the Moodle-based training program is established by the analysis of scientific works on the issue. The group of methods also included modeling, method of exercises, method of programmed learning, micro-learning method, HTML5 technology is used to develop interactive content in the form of a plugin H5P for distance learning technology LMS Moodle, the basic program for editing audio-video materials “Video Editor” (Windows 10).Results. The authors specified the term “audio-visual receptive activity” and described the results of the selection process of the educational content for teaching listening in the context of multimodal communication in English. The matrix of the training program is presented, a set of exercises is described, the use of which is designed to ensure the success of the formation of skills and the development of skills to ensure the effectiveness of perception and understanding in the context of multimodal communication, an example of the development of an interactive audio-visual exercise using basic and additional LMS Moodle plugins is given.Conclusion. The described training program acts as a technological core of a method of teaching listening in the context of multimodal communication in English and is aimed at ensuring a partial automatization of the developmental process of the specific receptive and interpretative skills that Russian high school students require to participate both actively and effectively in intercultural multimodal communication in English.